Phytotoxicity of extracts and fractions of Ouratea spectabilis (Mart. ex Engl.) Engl. (Ochnaceae) - Mecina, Gustavo Franciscatti [UNESP]; Santos, Valter Henrique Marinho dos [UNESP]; Dokkedal, Anne Lígia [UNESP]; Saldanha, Luiz Leonardo [UNESP]; Silva, Luciana Pereira; Silva, Regildo Márcio Gonçalves da [UNESP] (Elsevier, 2014)
Among the numerous plant species occurring in the Cerrado, Ouratea spectabilis stands out because of the lack of species that grow beneath its canopy. Therefore, this study aimed to evaluate the phytotoxic potential of different extracts and fractions of the hydroethanolic extract from leaves of O. spectabilis through laboratory bioassays of the pre-and post-emergence of seeds of Lactuca sativa L., determination of the mitotic index in root cells of Allium cepa L., antioxidant activity and phytochemical screening of different classes present in extracts and ethyl acetate fractions. It was possible to verify that different extracts and ethyl acetate fractions of O. spectabilis interfered with germination rates, as reduced germination was observed when compared with the control. Similarly, growth and development was affected in lettuce seedlings, as shown by the reduced length of primary roots and hypocotyls compared with the control. In addition, the mitotic index was reduced in treated groups compared with the negative control. HPLC-PAD analysis for both the hydroethanolic extract and its ethyl acetate fraction, showed a predominance of flavonoid compounds belonging to the groups of isoflavones and catechins in ethyl acetate fractions of hydroethanolic extracts. Thus, it was concluded that this species synthesizes phytotoxic compounds capable of interfering in the stabilization and development of other species.
Keywords: Phytotoxic; Allelopathy; Allelochemicals; HPLC-PAD; Allium cepa; DPPH